2013
DOI: 10.1371/journal.pone.0085046
|View full text |Cite
|
Sign up to set email alerts
|

Human Surfactant Protein D Alters Oxidative Stress and HMGA1 Expression to Induce p53 Apoptotic Pathway in Eosinophil Leukemic Cell Line

Abstract: Surfactant protein D (SP-D), an innate immune molecule, has an indispensable role in host defense and regulation of inflammation. Immune related functions regulated by SP-D include agglutination of pathogens, phagocytosis, oxidative burst, antigen presentation, T lymphocyte proliferation, cytokine secretion, induction of apoptosis and clearance of apoptotic cells. The present study unravels a novel ability of SP-D to reduce the viability of leukemic cells (eosinophilic leukemic cell line, AML14.3D10; acute mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…Our data corroborate previous studies in which SP‐D was shown to bind eosinophils in a maltose and Ca ++ ‐dependent manner . SP‐D also inhibited eotaxin‐induced migration, degranulation of eosinophil cationic protein and promoted apoptosis upon IL‐5 priming in vitro …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our data corroborate previous studies in which SP‐D was shown to bind eosinophils in a maltose and Ca ++ ‐dependent manner . SP‐D also inhibited eotaxin‐induced migration, degranulation of eosinophil cationic protein and promoted apoptosis upon IL‐5 priming in vitro …”
Section: Resultsmentioning
confidence: 96%
“…39 SP-D also inhibited eotaxin-induced migration, degranulation of eosinophil cationic protein 39 and promoted apoptosis upon IL-5 priming in vitro. [40][41][42] SP-D exerts both host-defense and anti-inflammatory functions in the lung. These are not contradictory as they both serve immune protection of the respiratory mucosa through distinct and complementary mechanisms as we and many others have previously shown.…”
Section: Sp-d Inhibited Eosinophil Activation and Blocked Formation Omentioning
confidence: 99%
“…Rest of the SP-D strongly associated with the beads was eluted with 20 mM EDTA in 20 mM Tris-HCl, pH 7.4 at room temperature with mild shaking for 1 h. Supernatant collected after MnCl 2 elution contained SP-D proteins only, while EDTA eluted fractions contained both SP-A and SP-D proteins and they were further separated by gel filtration and analyzed by silver staining ( Fig.S3.i ) and Western blot respectively ( Fig S3.ii ). The purified nSP-D protein was assayed for endotoxin content (given below), its binding and ability to agglutinate A. fumigatus conidia and its potential to enhance killing of fungal conidia by human PBMCs in vitro [31] .…”
Section: Methodsmentioning
confidence: 99%
“…17 In this study, we have used recombinant human SP-D expressed in E. coli, which consists of three CRDs, a neck and eight gly-Xaa-Yaa collagen region repeats, where Xaa and Yaa could be any amino acid. 31,46,47 Thus, interaction between SP-D and nanoparticles can have profound and wide-ranging impact on the pulmonary innate and adaptive immune mechanisms. 41 This ligand binding causes opsonic effects, leading to enhanced phagocytosis and clearance mechanisms via superoxidative burst and mostly pro-inflammatory immune response by phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%